Improving Understanding of Students Digestive Concepts with PALED 3D Learning Media - Muhamad Khanafi; Siti Alimah (Universitas Negeri Semarang, 2025)
The 3-dimensional LED board of the digestive system (PALED 3D-SD) is a learning media that was developed on the basis of analyzing the problems and needs of students. Based on the results of observations in the field, students still have difficulty in learning, especially in understanding the concept of the human digestive system material so that it has an impact on learning outcomes that are not optimal. This is due to the character of the material of the digestive system that cannot be sensed directly by the five senses of students. The learning media used so far have not optimally facilitated students' understanding of concepts. The availability of visual media (torso) of the human digestive system in schools has not been able to display a wide range of material, namely showing the flow of human digestive bioprocesses. This study aims to analyze the validity of the PALED 3D-SD media developed according to media experts and material experts, analyze the practicality of the media according to teachers and students, and analyze the effectiveness of the media in improving students' conceptual understanding through indicators of N-gain test results, class classical completeness, and average difference test. This research is a type of R&D (research & development) research using the ADDIE model through the analysis, design, development, implementation, and evaluation. The validity test of PALED 3D-SD media was obtained from the assessment of 2 media experts and 2 material experts. The practicality test of the media used samples from class XI MIPA 9 and teachers at SMA N 5 Semarang, while the media effectiveness test through a quasi-experimental design used samples from class XI MIPA 5 (control class) and XI MIPA 6 (experimental class) at SMA N 12 Semarang. The results of the media validity test show that the PALED 3D-SD media is very valid according to media experts and material experts. The results of the media practicality test show that the PALED 3D-SD media is considered very practical according to students and teachers. The results of the media effectiveness test show that PALED 3D-SD is effective in improving students' conceptual understanding based on the results of the N-gain test which is in the medium category, the results of classical class completeness are obtained by the percentage of completeness that has met the effective criteria and is higher than the control class, and the test results average difference statistic which shows that there is a difference in learning outcomes (concept understanding) between the group that learns to use PALED 3D-SD and the group that learns to use video. The conclusion based on this research is that the PALED 3D-SD media developed is valid, practical, and effective in improving students' conceptual understanding.